DEVELOPING A RUSSIAN-UZBEK PARALLEL CORPUS: CHALLENGES, METHODS, AND IMPLICATIONS FOR COMPARATIVE LINGUISTICS AND TRANSLATION STUDIES - Lolakhon Nigmatova Khamidovna (Galaxy International Interdisciplinary Research Journal, 2023)
In the realm of comparative linguistics and translation studies, the construction and deployment of parallel corpora have emerged as invaluable tools for nuanced linguistic analyses. This study delves into the intricate process of developing a Russian-Uzbek Parallel Corpus, highlighting the multifaceted challenges, methodological considerations, and potential avenues for research this endeavor unveils. Drawing upon corpus linguistics’ foundational methodologies, the research underscores the significance of such a corpus in addressing contemporary linguistic and translational challenges. The elaboration and magnitude of parallel corpora, especially within national confines, pave the way for rigorous comparative and typological investigations, spanning both lexical and grammatical dimensions. This paper also elucidates the paramount importance of developer competency in corpus construction, emphasizing that inaccuracies or misguided translations could gravely distort the intrinsic essence of source texts. One of the pivotal challenges broached is the development of methodologies and tools for lexical knowledge extraction, encompassing tasks like lexical unit recognition in texts and the formation of triads encompassing words, phrases, and translations. The exploitation of parallel texts is also advocated for the formulation of knowledge representation methods, the inception of specialized dictionaries, and the creation of multilingual concordances. Through an exhaustive analysis, it is revealed that parallel corpora facilitate the discernment of both semantic and discursive peculiarities of words, alongside illuminating their cross-cultural functional correspondences.